Achieving the fast track 90-90-90 and 95-95-95 targets in sub-Saharan Africa: A rapid review - Celenkosini T. Nxumalo; Usangiphile Buthelezi; Hlolisile Chiya; Mokgadi U. Makgobole; Nomakhosi Mpofana; Themba Mgwaba; Zamasomi Luvuno (Journal of Public Health in Africa)
Background: The Joint United Nations Programme on HIV/AIDS (UNAIDS) set targets for 95% of people living with human immunodeficiency virus (HIV) infection to know their status, 95% to receive antiretroviral therapy (ART) and 95% to achieve viral suppression. These targets mirror the 90-90-90 targets that were aimed to be met by 2020 to end AIDS as a public health threat by 2030.